Ecohydrological impacts of oil palm expansion: a systematic review. (7th March 2023) - Gómez, Angélica M; Parra, Adriana; Pavelsky, Tamlin M; Wise, Erika; Villegas, Juan Camilo; Meijide, Ana
Abstract: Global demand for vegetable oil and high oil palm yield have driven the rapid expansion of oil palm plantations in tropical countries. The research literature widely recognizes the effects of forest cover conversion into oil palm on biodiversity, deforestation, and carbon dynamics. However, research on the ecohydrological impacts of oil palm plantations is sparse, despite studies indicating that oil palm development may reshape land-water interactions and the availability and movement of water at different spatial and temporal scales. We address this gap by conducting a systematic literature review on oil palm development and its relation to ecohydrological processes. We found 139 relevant papers up to the year 2021, addressing different ecohydrological processes related to oil palm. We reviewed their spatiotemporal scales, geographic distribution, oil palm species and age, and the effects of land conversion from forest, cropland, and pastures. We also incorporated societal aspects regarding community perceptions of water. Our review highlights the effects of oil palm plantations on three main components of the water cycle: (i) land-atmosphere, (ii) fluvial systems, and (iii) soils and groundwater. Most studies include analyses of the Indo-Malayan and Australasian biogeographical regions (113), followed by the Neotropics (49) and the Afrotropics (15). Compared to rainforests, oil palm monocultures are warmer and drier. They have higher evapotranspiration (ET) rates, lower runoff regulation and infiltration capacity, and lower soil organic carbon (SOC). Although less often implemented, alternative oil palm management practices, including oil palm agroforestry, can help to mitigate some of these effects. Forest to oil palm conversion is the most studied land transition, while conversions from croplands, pastures, and grasslands are less studied. Overall, we identify gaps in understanding the long-term effects of management on ecohydrological processes under different land conversions, especially in the Neotropics and the Afrotropics, precluding research-informed policy to manage impacts of this expanding crop.